Hypertension in Japanese Americans: the Seattle Japanese-American Community Diabetes Study. - Fujimoto, W (1996)
AMONG SEATTLE'S JAPANESE AMERICANS, hypertension is associated with older age, male gender (in the younger age groups), glucose intolerance (impaired glucose tolerance and diabetes), and visceral obesity (measured by computed tomography). The gender difference in prevalence of hypertension is absent in those ages 65 to 74 and in those with diabetes. In the absence of diabetes, hypertension is not associated with fasting plasma insulin levels in the older second generation, but it is in the younger third generation. The association of hypertension with plasma insulin in the third generation may be due to the association between diabetes and plasma insulin and the presence of many prediabetic individuals in this generation. About three-fourths of Japanese Americans are aware of their hypertension, slightly more than half of hypertensive Japanese Americans are being treated with anti-hypertensive medication, and of those receiving anti-hypertensive medication, less than half have their hypertension controlled. Women tend to be less aware of hypertension, to receive anti-hypertensive medication less often, and to have their hypertension less well-controlled than men.